Decision makers' perspectives on implementation of governance attributes in the Kenyan Department of Health: a qualitative review in Uasin Gishu County. (April 2017) - Sitienei, Jackline C; Nangami, Mabel; Manderson, Lenore; Paina, Ligia; Kosgei, Rose
Abstract: Background: Health care systems in low-income and middle-income countries, including Kenya, often perform poorly. Governance is increasingly recognised as an important factor in health system performance. However, conceptually and practically, governance remains poorly understood and difficult to measure. Attributes of good governance practices include transparency, equity, accountability, community participation and consensus orientation, setting shared directions, regulation and oversight, and the use of intelligence and information. The purpose of this paper is to examine the extent to which good governance attributes have been implemented by policy makers and managers of primary healthcare facilities in Uasin Gishu County, Kenya. Methods: Between April and July, 2016, we administered a survey to 108 decision makers at the constitutional level of governance in the department of health, Uasin Gishu County. We reviewed documents and collected data on practices of good governance using a 42-question self-administered structured questionnaire with open questions, and an adapted five -point Likert-type scale. We calculated proportions of level of agreement to establish the decision makers' perceptions on the extent of implementation of good governance practices. Cronbach's α for the items was between 0·7172 and 0·8421. We used factor analysis to identify latent factors. Qualitative information was coded and categorised into emerging themes. Findings: Data were collected between April and July, 2016. 93 people responded, of whom 42 (45%) were women. 58 respondents (64%) were older than 41 years; 64 (74%) had a degree qualification and 69% had been in their current positions for less than 5 years. About half of respondents agreed on good governance practices in strategic vision (51 [55%]) and regulation and oversight (50 [54%]). Respondents thought there was some effort, but that it was not good enough in implementing good practices in intelligence and information (51 [55%]), transparency (36 [39%]), participation and consensus orientation (44 [47%]), and respondents reported their belief that there were poor practices in accountability (64 [69%]) and equity (60 [65%]). The overall governance score was not good enough at 48% with only 9 respondents (10%) agreeing there were good governance practices. Though governance is mentioned in the strategic and development plans, there are no clear mechanisms of implementation and evaluation of governance attributes. Corruption, nepotism, lack of transparency, political interference and inadequate use of information affected governance performance. Interpretation: Our findings suggest that it is feasible to assess implementation of governance attributes in primary health care and we provide insight on strong and weak governance attributes. Overall, decision makers of Uasin Gishu County gave a poor score for governance of public health facilities. Structures should be put in place to improve accountability, equity, and community participation. Funding: Consortium for Advanced Research Training in Africa (CARTA); Future Health Systems.